Hubungan Faktor Lingkungan Dengan Kejadian Ispa Non Pneumonia Pada Balita: THE RELATIONSHIP OF ENVIRONMENTAL FACTORS WITH THE INCIDENT OF NON-PNEUMONIA ACUTTE RESPIRATORY TRACT INFECTIONS IN TODDLERS - Naya Ernawati; Fitriana Kurniasari Solikhah (Jurnal Keperawatan Terapan, 2024)
Acute Respiratory Infections (ARI) are the main cause of morbidity and mortality in children under five. ISPA always ranks first among the 10 most common diseases in Indonesia. To be able to overcome the spread of ISPA, it is necessary to know the risk factors for ISPA incidents. The aim of this study was to analyze the relationship between environmental factors and the risk of recurrent non-pneumonic ARI in toddlers in the Dinoyo health center working area, Malang City. Method: This type of research is descriptive analysis with a cross sectional approach. Data collection was carried out using a questionnaire. The population is parents of toddlers in the working area of ??the Dinoyo Health Center, Malang City. This research used purposive sampling, with a sample size of 60 respondents. Data analysis was carried out univariately, bivariately with the chi square test. Results: The results of the study showed that the incidence of recurrent non-pneumonic ARI in toddlers had a significant relationship with ventilation (p value = 0.028; OR = 0.29), smoking in the house (p value = 0.000; OR = 7.56). Recommendations require further research to develop a model for preventing recurrent non-pneumonic ARI in toddlers according to the risk factors found.